Human Platelet Lysate Acts Synergistically With Laminin to Improve the Neurotrophic Effect of Human Adipose-Derived Stem Cells on Primary Neurons in vitro - Guiotto, Martino; Raffoul, Wassim; Hart, Andrew M.; Riehle, Mathis O.; di Summa, Pietro G. (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Despite the advancements in microsurgical techniques and noteworthy research in the last decade, peripheral nerve lesions have still weak functional outcomes in current clinical practice. However, cell transplantation of human adipose-derived stem cells (hADSC) in a bioengineered conduit have shown promising results in animal studies. Human-Platelet-Lysate (hPL) has been adopted to avoid foetal bovine serum (FBS) in consideration of the biosafety concerns inherent with the use of animal-derived products in tissue processing and cell culture steps for translational purposes. In this work we investigate how the interplay between hPL-expanded hADSC (hADSChPL) and Extra-cellular Matrix (ECM) proteins influence key elements of nerve regeneration. Methods: hADSC were seeded on different ECM-coatings (Laminin, LN; Fibronectin, FN) in hPL (or FBS)-supplemented medium, and co-cultured with primary Dorsal Root Ganglion (DRG) to establish the intrinsic effects of cell-ECM contact on neural outgrowth. Co-cultures were performed “direct”, where neural cells were seeded in contact with hADSC expanded on ECM coated substrates (contact effect) or “indirect”, where DRG were treated with their conditioned medium (secretome effect). Brain-derived Nerve Factor (BDNF) levels were quantified. Tissue culture plastic (TCPS) was used as control substrate in all experiments. Results: hPL as supplement alone did not promote higher neurite elongation than FBS when combined with DRG on ECM substrates. However, in presence of hADSC, hPL could dramatically enhance the stem cells effect with increased DRG neurite outgrowth when comparing to FBS conditions, regardless of the ECM coating (in both indirect and direct co-cultures). The role of ECM substrates in influencing neurite outgrowth, was less evident in the FBS conditions, while it was significantly amplified in presence of hPL, showing better neural elongation in LN conditions when compared to FN and TCPS. Concerning hADSC growth factors secretion, ELISA showed significantly higher concentrations of BDNF when cells were expanded in hPL compared to FBS-added medium, without significant differences between cells cultured on the different ECM substrates. Conclusions: This data suggest how hADSC grown on LN and supplemented with hPL could be active and prone to support neuron-matrix interactions. hPL enhanced hADSC effects by increasing both proliferation and neurotrophic properties, including BDNF release.